Opinions, Problems, and Expectations of Participants in Informal Religious Education Services for Hearing- and Visually-impaired People - Banu Gürer; Elif Kaya (Darulfunun Ilahiyat)
Disability is a situation and process that includes difficulties in rationalizing and coping with it on the part of individuals with disabilities and their families. It can be said that religion has an important place among the ways used to make sense of the situation in question and to cope with the process. This is because religion is a resource that can provide the spiritual strength needed for people to cope with the situation they are in, by giving answers to people to make sense of the situation they are in. One of the basic elements that bring this function of religion to life is religious education. The main institution that organizes informal religious education activities for people with disabilities in Turkey is the Presidency of Religious Affairs. This study aims to understand the problems and expectations of hearing- and visuallyimpaired individuals who take part in the informal religious education given to people with disabilities in the Qur’an courses in the Presidency of Religious Affairs. The research is structured with a phenomenological pattern. Interviews consisting of semi-structured questions were used to obtain the data. Thirty people, 15 of whom were hearing impaired and 15 visually impaired, participated in the interviews. The data were analyzed with descriptive analysis and content analysis techniques. The results of the research were evaluated in four dimensions: the sources of the religious education of the participants, their coping with disability and the effect of religion, their religious education needs, and their expectations from the Qur’an courses in which they receive non-formal religious education in line with these needs.